Study of bases influence on the biopharmaceutical characteristics of the pastes for onychomycosis therapy - V. V. Luc; V. V. Gladyshev; A.P. Lisyanskaya; A.D. Diudiun (Zaporozhye State Medical University, 2018)
According to the European and American authors the onychomycosis prevalence in the world has amount from 8.0 % to 26.9 %. Topical treatment of onychomycosis in most cases is the only acceptable method of therapy mainly due to high safety. Etiotropic topical pharmacotherapy of this pathology is carried out by the dermatomicotic medicines - creams, ointments, gels, solutions. Nail polishes are the specific dosage forms for onychomycosis therapy. However antimycotic polish therapy is sufficiently effective only in case of treatment the surface white and distal-lateral form of onychomycosis, but just in case when less than 1/3 of nail plate is affected. Also wide application is limited to length of use (from 6 month to 1 year) and high therapy cost. According to above mentioned information, development of specific semisolid dosage form for onychomycosis therapy without removing the nail plate and allowing combination high efficacy of medical substances even in case of nail-bed affection, rational term of treatment and economical availability is rational. Presence of these effects may be reached by the way of combination in semisolid dosage form for appliication on the nail plate - the paste - substances with keratolytic and antimycotic action. At the same time use of acid combination as a keratolytic for pH decreasing in tissue of the nail plate and fungi growth inhibition and also providing with penetration of active components of paste for onychomycosis therapy. As a result of this development of semisolid dosage form for the topical treatment of onychomycosis with biologically active substances from the group of nonspecific antimycotics (2-mercaptobenzthiazol, chinozol) with broad spectrum of antimycotic, antibacterial activity and safety has a scientific and practical interest. The aim of this work is biopharmaceutical substantiation of optimal base for semisolid dosage form - paste for etiotropic therapy of onychomycosis. Materials and methods. As a device for developing pharmacotherapeutical preparation hydrofobic and emulsion bases resistant to combination with sufficiently aggressive keratolytics and described in literature were studied. As an active pharmaceutical ingredient for antimycotic paste 2-mercaptobenzthiazol and chinozol in concentration 10% and 10% accordingly for providing with the optimal level of antifungal activity were used. As keratolytic substances traditionally used for onycholysis: carbamide, mixture of salicylic and benzoic acids in concentration described in literature were used. At the same time chinozol shows keratolytic effect and in that capacity is used in formulations of chinozolo-salicylic, chinozolo-dimexidic and also carbamidic plasters for nails. The content of dry substances and plasticizers in formulations of onycholytic pastes was chosen taking into account the requirements of Ukrainian Pharmacopoea and normative document for this dosage form. Taking into account the advisability of high dispersion degree of medical substances in semisolid dosage forms for external use and physical-chemical properties of 2-mercaptobenzthiazol the latter was added in emulsion bases after preliminary dissolution in polyethylenoxyde 400 with heating. Keratolytics were added as a suspension in all bases. Investigations of scientifically substantiation of the base of paste for onychomycosis therapy were carried out according to plan of single-factor analysis of variance with repeated observations. For all selected compositions the releasing of active pharmaceutical ingredients (2-mercaptobenzthiazol and chinozol) from ointments were studied with equilibrium dialysis method by Kruvchinsky at the temperature 25.0 ± 0.5 °С (temperature on the surface of nail) through the semipermeable film "Kuprofan" in the Franz diffusion cell apparatus (producer PermeGear, Inc., USA). As a dialysis medium taking into account 2-mercaptobenzthiazol solubility was used solution containing methanol and water 1:1 and chinozol releasing was carried out into water. Concentration of active pharmaceutical substances released from experimental pastes after 2 hours was determined spectrophotometrically. Results. Carried out verification of average results of 2-mercaptobenzthiazol and chinozol releasing by the Dunkan's multiple rank test allowed to build the preferred series of pastes base influence on the intensity of active pharmaceutical ingredients releasing. Obtained results showed the sighnificant advantage of the emulsion ointment base providing with optimal level of 2-mercaptobenzthiazol and chinozol releasing from experimental compositions of semisolid dosge forms for onychomycosis therapy. Conclusions. It was determined that sort of the base makes a sighnificant influence on 2-mercaptobenzthiazol and chinozol releasing from the antimycotic pastes for onychomycosis therapy. Variance analysis of results revealed that emulsion vehicle containing acid-resisting emulsifier provides with optimal 2-mercaptobenzthiazol and chinozol releasing.